The drive to the finish line
The race is almost over, but the body hurts so much that you are not sure that you can maintain or even increase your effort from now to the line. How are you going to muster up the courage and strength to hold off the runner breathing down your neck? The way that you do this is to forget about the others and get back to the basics. These basics are: ARMS: Drive the arms as fast and hard as possible--the feet will follow. The hands should go up to at least chin level and should go at least as far as the hip on the down-swing. The downward drive should be forceful to help drive the foot into the track. LEGS: The quads are probably starting to tie-up at this point so relax them. This is tough to do, but by concentrating on it for a stride or two, it will help. FEET: When fatigued, there is a tendency to float, so get the feet back down onto the track as quickly as possible. This couples with the fast arm/hand drive to produce a faster turn rate. SURGE: At this point in a maximum effort race, the body will usually be slowing. To overcome this, you have to surge. To do this, use the "in & out" technique. The "in" portion will only last three or four strides. Hold your breath, lean slightly forward and try to accelerate. On the "out" portion, come back to the full upright running form, breathe normally and try to maintain your speed. You may want to go through this cycle three or four times on the way to the line. DORSIFLEX: Avoid coming too far up on your toes when you surge. Running on the toes rather than dorsiflexed disables the ability of the calf muscle to help in the push-off and makes the hams carry all of the load. Accelerating while up on the toes can lead to serious hamstring tears. Don't wait until the race to try this. Practice it so that it becomes almost automatic.